Stem Cell Basis for Fractal Patterns: Axillary Meristem Initiation - Wang, Ying (Frontiers in Plant Science, 2021)
Whereas stem cell lineages are of enormous importance in animal development, their roles in plant development have only been appreciated in recent years. Several specialized lineages of stem cells have been identified in plants, such as meristemoid mother cells and vascular cambium, as well as those located in the apical meristems. The initiation of axillary meristems (AMs) has recently gained intensive attention. AMs derive from existing stem cell lineages that exit from SAMs and define new growth axes. AMs functions as the embryonic SAM and forms additional rounds of AMs, creating a fractal branching pattern. Their formation takes place in leaf-meristem boundaries and mainly comprises two key stages. The first stage is the maintenance of the meristematic cell lineage in an undifferentiated state. The second stage is the activation, proliferation, and re-specification to form new stem cell niches in AMs, which become the new postembryonic ‘fountain of youth’ for organogenesis. Both stages are tightly regulated by spatially and temporally interwound signaling networks. In this mini-review, I will summarize the most up-to-date understanding of AM establishment and mainly focus on how the leaf axil meristematic cell lineage is actively maintained and further activated to become CLV3-expressed stem cells, which involves phytohormonal cascades, transcriptional regulations, epigenetic regulations, as well as mechanical signals.